DECISION FACTORS FOR CHOOSING AIRPORT RAIL LINK TRANSIT - ลบแย้ม, สญชัย (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2018)
The research aimed to study all potential socio-economic factors affecting passengers riding a Thai mass transit system “Suvarnabhumi Airport Rail Link,” generally known as Airport Link or ARL.The ARL has eight stations starting from Suvarnabhumi to Phayathai and operates two lines for service. Those lines are City Line and Express Line. The project launched about eight years ago, and since then the transit has experienced ridership lower than previously planned by approximately forty percent. Initially, the project had estimated average daily ridership of both lines as 50,000 passengers including 48,000 passengers for the City Line and 2,000 for the Express Line respectively, while the collected data showed the average daily passengers merely 30,000 that was composed of 29,000 City Line riders and 1,000 Express Line riders. As such the statistical data, the ARL is really in needs of finding short-term measures to increase the daily ridership to cover such a huge loss. This study research for potential socio-economic factors promoting ridership of the ARL. The research indicates four variables statistically significant affecting travel choice of regular passengers. Those variables include the followings: 1) age 2) income 3) dependents and 4) household vehicle ownership.